Hashimoto's thyroiditis as a risk factor for thyroid cancer. Issue 5 (October 2020) - Feldt-Rasmussen, Ulla
Abstract : Purpose of review: To summarize the recent developments in considering Hashimoto's thyroiditis as a risk factor for thyroid cancer. Recent findings: Modern approaches to understanding the co-occurrence of Hashimoto's thyroiditis and thyroid cancer have consistently found increased prevalence of both conditions, separately as well as of their coexistence. The inflammatory process in Hashimoto's thyroiditis is understood as a potential risk factor for thyroid cancer development. This has also provided a better understanding of the limitations in the current diagnostic and follow-up armamentarium for both conditions, resulting in international guidelines from the clinical and scientific societies. Other recent developments call for a paradigm shift in guidelines on thyroid carcinomas when lymphocytic infiltration is present, which potentially should always be considered the case at least in areas of sufficient iodine intake. Summary: The literature of Hashimoto's thyroiditis as a risk factor for thyroid cancer is reviewed over the last year to highlight new developments in the understanding of their association and future clinical implications.